Development of an ISSR-derived SCAR marker linked to apospory in buffel grass (Cenchrus ciliaris L.) - Dwivedi, Krishna Kumar; Radhakrishna, A.; Kumar, S.; Srivastava, M.K.; Gupta, M.G.; Kaushal, P. (The Indian Journal of Genetics and Plant Breeding, 2016)
Cenchrus ciliaris (buffel grass) is a valuable forage grass, reproducing through aposporous apomixis. Inter Simple Sequence Repeat (ISSR) markers converted to SCAR marker linked to apospory in this crop is reported. Out of twentyfive ISSR primers tested in DNA bulks from apomictic and sexual progenies,five primers detected polymorphism.The 1.1 kb amplicon derived from the primer ISSR-856 showed co-segregation with apomictic mode of reproduction. Accordingly, a pair of SCAR (Sequence Characterized Amplified Region) primers were designed which also generated a 1.1kb amplicon (Apo-856) only in the apomictic plants. Importance of such molecular markers in genetics and breeding of C. ciliaris is discussed.